Galantamine as a preventive of diisopropylphosphorofluoridate toxicity effects in rat brain - Saghafi, M. M; Živin, M; Pregelj, P (Folia biologica (Praha), 2013)
Diisopropylfluorophosphate exerts its toxic effect by irreversibly inhibiting acetylcholinesterase. This results in over-stimulation of central and peripheral cholinergic activity. The aim of the present study was to evaluate the possible preventive effects of acute treatment with reversible acetylcholinesterase inhibitor galantamine against the signs of cholinergic toxic syndrome provoked by diisopropylfluorophosphate, such as hypothermia, muscular fasciculations, oral dyskinesia and decreased locomotor performance in a rat model of intoxication. The effects of these two anticholinesterases on acetylcholinesterase activity and on the expression of mRNA of the immediate early response gene c-fos in the brain were assessed by histochemical acetylcholinesterase staining and by in situ hybridization, respectively. Diisopropylfluorophosphate induced rapidly progressing hypothermia, muscular fasciculations, oral dyskinesia and decreased locomotor performance. The increased cholinergic cortical and hippocampal activity due to irreversible acetylcholinerase inhibition were indicated by the increased c-fos mRNA autoradiographic signal and by the inhibition of acetylcholinesterase staining, respectively. Galantamine by itself provoked transient and relatively weak inhibition of the acetylcholinesterase staining, while it did not induce increased c-fos mRNA expression or significant behavioural signs of cholinergic toxicity. Galantamine significantly reduced the rate of the onset, but not the maximal hypothermia induced by diisopropylfluorophosphate. Importantly, all the above-mentioned behavioural and neurochemical effects of diisopropylfluorophosphate were significantly reduced by galantamine. These results indicate that the acute pre-treatment with galantamine may have prophylactic effects against the intoxication by diisopropylfluorophosphate.
Keywords: Animals; Acetylcholinesterase; isofluorofát; Rats; pohybové poruchy; tělesná teplota; Rats, Wistar; Isoflurophate; protoonkogenní proteiny c-fos; pohybová aktivita; fascikulace; Proto-Oncogene Proteins c-fos; messenger RNA; mozek; RNA, Messenger; Galantamine; regulace genové exprese; galantamin; Male; Body Temperature; Neuroprotective Agents; acetylcholinesterasa; Brain; krysa rodu Rattus; Motor Activity; Gene Expression Regulation; zvířata; mužské pohlaví; Movement Disorders; Fasciculation; potkani Wistar; neuroprotektivní látky